2018
DOI: 10.1093/cid/ciy160
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure Prophylaxis Initiation and Retention in Care Over 5 Years, 2012–2017: Are Quarterly Visits Too Much?

Abstract: Retention in preexposure prophylaxis (PrEP) care is critical to elimination of human immunodeficiency virus. We reviewed all Howard Brown Health patients receiving PrEP (n = 5583) from 2012 to 2017. Among those with 12 months of follow-up, 43% remained in care, yet only 15% had all 4 quarters with a PrEP visit. Insurance status and comorbid conditions were drivers of retention in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 9 publications
6
53
2
Order By: Relevance
“…56,57 This may be due, in part, to the guidelines for PrEP initiation and monitoring that can be prohibitive for key populations. [58][59][60][61] Scaling out of PrEP to YBMSM will require considering novel and adapted delivery methods. One strategy to address barriers involves expedited (same day start) PrEP, both within and outside of traditional health care settings.…”
Section: Prep: Scaling Out Of a Biomedical Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 This may be due, in part, to the guidelines for PrEP initiation and monitoring that can be prohibitive for key populations. [58][59][60][61] Scaling out of PrEP to YBMSM will require considering novel and adapted delivery methods. One strategy to address barriers involves expedited (same day start) PrEP, both within and outside of traditional health care settings.…”
Section: Prep: Scaling Out Of a Biomedical Interventionmentioning
confidence: 99%
“…A "one size fits all" method for PrEP delivery should be reassessed since younger populations may need more frequent interactions to encourage adherence, while older populations may not. 60,61 Implementation research methodologies can be applied to test these hypotheses and provide "differentiated" care based on individual client needs.…”
Section: Prep: Scaling Out Of a Biomedical Interventionmentioning
confidence: 99%
“…Pre‐exposure prophylaxis (PrEP) is a highly effective biomedical prevention strategy when taken during periods of HIV risk [1,2]. Although PrEP persistence (sustained PrEP use over time) was high among PrEP users in clinical trials and early demonstration projects [2‐4], it has been variable among later PrEP adopters and in real‐world evaluations, with 15 to 62% of users discontinuing PrEP by six months [5‐14]. Prevention‐effective adherence is a concept which describes the importance of using PrEP during periods of HIV risk, as compared to antiretroviral therapy, for which lifelong adherence is required [15].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In addition, required quarterly follow-up clinic visits and laboratory testing have been considered a potential barrier to longer term persistence in PrEP care. [11][12][13][14][15] Indeed, a recent study conducted in San Francisco, a location with robust PrEP care, found that the most common reason for discontinuation was difficulty attending clinic visits or completing laboratory tests. 16 Technological innovations in PrEP delivery systems may help address structural and social challenges related to PrEP uptake and continuity, such as fear of discrimination on the basis of one's sexual identity, difficulty attending clinic visits, or completing laboratory testing.…”
Section: Introductionmentioning
confidence: 99%